Impact of genetic polymorphisms on paediatric atopic dermatitis. (September 2015) - Esposito, Susanna; Patria, Maria Francesca; Spena, Silvia; Codecà, Claudio; Tagliabue, Claudia; Zampiero, Alberto; Lelii, Mara; Montinaro, Valentina; Pelucchi, Claudio; Principi, Nicola
In order to investigate whether polymorphisms of genes encoding some factors of innate and adaptive immunity play a role in the development of, or protection against atopic dermatitis (AD) and condition its severity, we genotyped 33 candidate genes and 47 single nucleotide polymorphisms (SNPs) using Custom TaqMan Array Microfluidic Cards and an ABI 7900HT analyser (Applied Biosystems, Foster City, CA, USA). The study involved 104 children with AD (29 with mild-to-moderate and 75 with severe disease; 42 girls; mean age ± SD, 5.8 ± 3.3 years) and 119 healthy controls (49 girls; mean age, 4.8 ± 3.0 years). IL10-rs1800872T, TG and MBL2-rs500737AG were all significantly more frequent among the children with AD ( P = 0.015, P = 0.004 and P = 0.030), whereas IL10-rs1800896C and TC were more frequent in those without AD ( P = 0.028 and P = 0.032). The VEGFA-rs2146326A and CTLA4-rs3087243AG SNPs were significantly more frequent in the children with mild/moderate AD than in those with severe AD ( P = 0.048 and P = 0.036). IL10-rs1800872T and TG were significantly more frequent in the children with AD and other allergic diseases than in the controls ( P = 0.014 and P = 0.007), whereas IL10-rs1800896TC and C were more frequent in the controls than in the children with AD and other allergic diseases ( P = 0.0055 and P = 0.0034). These findings show that some of the polymorphisms involved in the immune response are also involved in some aspects of the development and course of AD and, although not conclusive, support the immunological hypothesis of the origin of the inflammatory lesions.